Calcineurin Inhibitor Agents Interact Synergistically with Antifungal Agents In Vitro against Cryptococcus neoformans Isolates: Correlation with Outcome in Solid Organ Transplant Recipients with Cryptococcosis - Kontoyiannis, Dimitrios P. (American Society for Microbiology (ASM), 2008)
Synergistic interactions were observed between CIs and antifungal agents against 53 (90%) of 59 Cryptococcus neoformans isolates from solid organ transplant recipients with cryptococcosis and may account for better outcomes in patients with cryptococcosis receiving these immunosuppressive agents.